FIGURATIVE COMPONENT OF THE "ALGARROBO" CONCEPT IN ARGENTINE FOLKLORE - Lomakina , Irina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The concept of algarrobo in Argentine folklore is a mental structure that reflects an understanding of reality. It affects the way in which the surrounding world is perceived and facilitates interaction with this surrounding world. The article clarifies the role of the figurative component of the concept of algarrobo in the formation of the linguistic picture of the world of Argentines through folklore, studies the interpretations through which this influence takes place, investigates how language and the concept of algarrobo interact and are interconnected. In the cognitive space of every country there are plants which are symbols of the homeland. They symbolize her beauty, serve as talismans in times of trouble, protect, give health, strength and inspiration, comfort during being in other lands. Such is the carob tree (algarrobo) in Argentine folklore. The algarrobo concept occupies a prominent place in the Argentine cognitive-linguistic picture of the world, because it is a universal national and spiritual cognitive unit. The use of the algarrobo concept gives the discourse a certain cognitive coloring, namely, it conveys such images as: homesickness, a symbol of the native area, "my home", "my yard", "my little homeland", "my area where these trees grow", definition of national identification. As a symbol of the native place, algarrobo evokes images of happiness, joy, satisfaction, inner warmth. In addition, algarrobo is a sign of certain events in the homeland. Also, in the language picture of the world of Argentine folklore, the algarrobo concept has inherent anthropomorphic features. "A tree is a person." A tree can feel everything that a person feels, make human movements. The use of age-related epithets añoso, añejo, viejo indicates that the image of the algarrobo concept has a stable symbolic counterpart: associatively with a person, one can talk about old age, wisdom, experience and memory. ______________ References: • Dzherіh O. S. «Koncept» u suchasnіj kognіtivnіj lіngvіsticі ta lіngvokul’turologії: ponjattja ta struktura Tipologіja movnih znachen’ u dіahronіchnomu ta zіstavnomu aspektah 35–36 (Vіnnicja, 2018): 61-69. • Prihod’ko, A. M. Koncepti і konceptosistemi v kognіtivno-diskursivnіj paradigmі lіngvіstiki (Zaporіzhzhja: Prem’єr, 2008), 332. • Cairati E. Historia cultural del algarrobo, desde la cuenca del Mediterráneo hasta la Costa Norte de Perú. Otras Modernidades 10–11 (Universidad de Milano, 2013): 186-204. • https://acordes.lacuerda.net/busca.php?exp=algarrobo&canc=0&ord=0&ini=0 • https://www.cancioneros.com/letras/buscar.php?CT=algarrobo&x=11&y=16